(untitled) (Fiep Bulletin - online, 2011)
This study aimed to diagnose motor delays of 80 children of both sexes, with 36 boys and 44 girls aged nine years, enrolled in the 4th year of primary education in public schools. All subjects were evaluated according to the two-dimensional model of Ozmum and Gallahue (2005), which classifies the fundamental motor skills in three stages: initial, elementary and mature. The skills tested were horizontal jump, lateral, rolling the body, balancing on one foot, throwing and kicking, so two movements in each category stabilizing, locomotor, manipulative, respectively. The data were presented in values of central tendency (mean), dispersion (standard deviation) and descriptive analysis, initially suffering a normality test of Shapiro-Wilking. The data showed a non-normal distribution and so we used the Mann-Whitney test for comparison between genders. All tests were performed in the computer software SPSS 14.0 for Windows, with the significance level of p <0.05 for comparison between genders. The data suggest that: (1) most boys and girls lag behind in relation to motor all motor skills tested, (2) boys and girls show locomotor performance lateral similar but boys show superiority to move the horizontal jump, ( 3) manipulative boys show higher performance than those of girls, (4) boys show performance stabilizer bearing upper body, although the two genera present motor delay, however statistical analysis showed superiority of the girls the ability to balance on one foot. Opportunities for teaching practices are essential for the development engine. The activities of physical education should provide education activities to develop the mature stage of fundamental motor skills.